2006
DOI: 10.1071/bt04221
|View full text |Cite
|
Sign up to set email alerts
|

Floral biology and late-acting self-incompatibility in Jacaranda racemosa (Bignoniaceae)

Abstract: Breeding-system studies have been conducted with 38 of the approximately800 species of Bignoniaceae, and self-incompatibility was found in 31 of these. In species for which the site of self-incompatibility barrier was studied, self-pollinated flowers consistently failed to develop into fruits, even though pollen tubes grew down to the ovary and penetrated most of the ovules. In this study, we have investigated the floral biology and the breeding system in Jacaranda racemosa Chamisso, with hand-pollination expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 25 publications
3
40
1
4
Order By: Relevance
“…The position of the anthers and stigma inside the petal hood promoted the pollen deposition on the upper head and thorax of the pollinators. The basal constriction of the corolla tube was compatible with long-tongued bees, such as Euglossa, as reported also by Bittencourt Júnior & Semir (2006). The same foraging behavior of these agents was registered in the pollination biology of Arrabidaea conjugata (Vell.)…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…The position of the anthers and stigma inside the petal hood promoted the pollen deposition on the upper head and thorax of the pollinators. The basal constriction of the corolla tube was compatible with long-tongued bees, such as Euglossa, as reported also by Bittencourt Júnior & Semir (2006). The same foraging behavior of these agents was registered in the pollination biology of Arrabidaea conjugata (Vell.)…”
Section: Discussionsupporting
confidence: 59%
“…It has been also suggested that the staminode may be used as a bridge by halictid bees to reach the anthers, eventually touching the stigma (Gottsberger & SilberbauerGottsberger 2006). It also retains pollen grains on the glandular hairs (trichomes), which are collected by bees (Morawetz 1982 apud Gottsberger & SilberbauerGottsberger 2006), and diminishes the space inside the corolla chamber, thus promoting better contact of the pollinators with the reproductive organs (Bittencourt Júnior & Semir 2006). In J. copaia, all those functions can be assumed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations